MODEL PENGEMBANGAN AGROINDUSTRI COCODIESEL DI DAERAH TERPENCIL - Irawadi Jamaran TIN (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACTThis paper presents a model for development of cocodiesel agroindustry in the remote and isolated areas. Using this new model both fishermen and coconut farmers can take advantages from the development of cocodiesel agroindustry. The price of coco-diesel will be lower than fossil diesel whereas the price of coconut will be increased. The fisrt part of this paper discusses in details about the feasibility and techno-economical analysis of the development of cocodiesel agroindustry in a remote area, that is the district of Aceh Singkil, in the Nanggroe Aceh Darussalam Province. Then a model for development of cocodiesel agroindustry by introducing a new approach namely “the poor helps the poor” will be presented in details. The results of this research indicate that the development of cocodiesel agroindustry using the “poor helps the poor” concept is very promising in the district of Aceh Singkil as well as for other remote areas in Indonesia.Keywords : coconut, agroindustry, cocodiesel, farmers, fishermen, income, saving, isolated, remote area, institutional